Abbess Hildegard of bingen (1098-1179): sequences and hymns - Page, Christopher 1952-; Hildegard of Bingen (Newton Abbot Antico edition)
This edition contains all the pieces by Hildegard which are labelled Sequentia in the two manuscript sources of her songs, together with O viridissima virga which should, perhaps, be classed as a sequence and Ave,generosa, one of Hildegard's finest hymns. Twelfth century sequences generally consisted of verses comprising a pair of versicles, each versicle being set to the same melody and the melody being different for each verse, producing a melodic form AA BB CC and so on. Contains: Columba aspexit Ave, generosa O ignis spiritus O lerusalem,aurea civitas O Euchari O viridissima virga O presul vere civitatis O Ecclesia O virga ac diadema Text of songs are included in both the notes and in poetic form in back.